Geotectonic Framework of Epithermal - / Mesothermal Gold Mineralisation Styles its Use in the Design of Exploration Methodology (The Australasian Institute of Mining and Metallurgy, 1990)
A new classification of subduction related (epithermal- / mesother-mal) gold mineralisation styles based on the tectonic framework they occur in, has been found helpful in practice. It offers a ratio-nalisation of exploration efforts during all stages of work.Methodology on the ground during first pass- and follow up explo-ration which has been found effective for the various mineralisa-tion styles is being briefly outlined.